2012
DOI: 10.1111/j.1524-475x.2012.00772.x
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes‐impaired wound healing and altered macrophage activation: A possible pathophysiologic correlation

Abstract: Macrophages play a critical role in wound healing and can be activated to two distinctive phenotypes in vitro: classical macrophage activation (caM) and alternative macrophage activation (aaM). This study investigated whether the impaired cutaneous repair observed in streptozotocin-induced diabetic rats was associated with altered macrophage activation. Our results show that macrophage activation phenotypes could be observed in wound healing through double immunostaining. The caM macrophages appeared in the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
86
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(95 citation statements)
references
References 34 publications
8
86
0
1
Order By: Relevance
“…Refractory diabetic wounds are characterized by a persistent inflammatory response, leading to impaired progression of the healing process [3, 11, 12, 16]. This study shows that the macrophage polarization status and expression of IL-6 significantly differ between non-diabetic and diabetic mice during pre-injury and in the early phase of wound healing.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Refractory diabetic wounds are characterized by a persistent inflammatory response, leading to impaired progression of the healing process [3, 11, 12, 16]. This study shows that the macrophage polarization status and expression of IL-6 significantly differ between non-diabetic and diabetic mice during pre-injury and in the early phase of wound healing.…”
Section: Discussionmentioning
confidence: 77%
“…Macrophage depletion and/or aberrant activation are known to result in impaired wound healing [12, 16, 34]. In diabetic wounds, we noted significantly increased expression of the macrophage marker CD68 at almost all time points, ruling out a role for macrophage depletion–associated impairment in diabetic wound repair [35].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Skin wound repair is divided into three phases: inflammation, epithelialization and remodeling [36]. Keratinocytes, macrophages and dermal fibroblasts is critical for this repair process [37][38][39]. Previous studies have demonstrated that activation of PPARδ in keratinocytes increased resistance of the keratinocytes to the apoptotic signals released during wounding, allowing faster re-epithelialisation [23,35], and activation of PPARδ in infiltrated macrophages attenuates the inflammatory response [31,34,40], which also promotes repair.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies report faster epithelialization in mice lacking innate immune cells (Dovi et al, 2003; Cooper et al, 2005), others unchanged healing (Martin et al, 2003), while models lacking macrophages demonstrate delayed tissue repair (Goren et al, 2009; Mirza et al, 2009). However, it becomes evident that the disappearance of inflammatory cells is required for healing to proceed, and that the persistence and/or the dysfunction of innate immune cells leads to impaired healing as exemplified by chronic inflammation in diabetic foot ulcers and chronic wounds (Khanna et al, 2010; Pukstad et al, 2010; Miao et al, 2012). …”
Section: When Things Go Wrongmentioning
confidence: 99%